The Effect of Multimodal Exercise on Fall Risk and Functional Ability in the Elderly with Frailty Syndrome with Type 2 Diabetes Mellitus - Rezki Syamsuriyana Halmu; Andi Ariyandy; Andi Wardihan Sinrang (Ghidza: Jurnal Gizi dan Kesehatan, 2023)
Elderly with Frailty Syndrome with Type 2 Diabetes Mellitus (T2DM) often experience loss of muscle mass and skeletal muscle function, causing a risk of falls and reduced functional abilities. To determine the effect of multimodal exercise on the risk of falls and functional ability in the elderly who experience frailty syndrome with T2DM. This research is quasi-experimental with a pretest-posttest design of 2 paired groups. A total of 50 older adults experiencing frailty syndrome with T2DM were divided into two groups of 25 people each. The T-Dependent Test and Wicoxon Test were used to determine changes before and after exercise administration, and the Mann-Whitney Test was used to determine the comparison between the intervention group and the control group. There was a reduced fall risk level and improved functional ability in the intervention group with Multimodal Exercise and in the control group (p=0.000). Multimodal Exercise had a difference in decreasing (Timed Up and Test) TUGT value higher than Elderly Gymnastics (p=0.001), and a higher increase in SPPB value was obtained in Multimodal Exercise than in the control group (p = 0.000). Multimodal Exercise intervention program was more effective in reducing fall risk and increasing functional ability.